2019
DOI: 10.24293/ijcpml.v26i1.1366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Concentration Difference between ST2 and NT-Pro BNP Before and After Ace-Inhibitors in NYHA III-IV Hearts Failure Patients

Abstract: Background: The American Heart Association (2016) stated that at the age of forty the risk of developing heart failure is one in five. Medication is based on clinical signs and symptoms that are often late. Early cardiac markers are required to guide therapy. This study compared the difference between ST2 and NT-ProBNP concentrations before and after ACE inhibitors (ACE-I) in NYHA III-IV heart failure patients.Method: This was a randomized prospective observational study without controls. The respondents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…ACEIs also induce the apoptosis of cardiac fibroblasts ( 76 ). A clinical trial from Maskito et al ( 77 ) showed the reduction of sST2 in heart failure patients. Wei Qiang-Tan et al also demonstrated similar effects of the ACEIs on reducing stimuli and activators of cardiac fibrosis; they showed the ACEIs effect on downregulating Smad and TGF-β activated kinase 1 in mice model ( 78 ).…”
Section: The Role Of Aceis In Cardiac Fibrosis In Rhdmentioning
confidence: 99%
“…ACEIs also induce the apoptosis of cardiac fibroblasts ( 76 ). A clinical trial from Maskito et al ( 77 ) showed the reduction of sST2 in heart failure patients. Wei Qiang-Tan et al also demonstrated similar effects of the ACEIs on reducing stimuli and activators of cardiac fibrosis; they showed the ACEIs effect on downregulating Smad and TGF-β activated kinase 1 in mice model ( 78 ).…”
Section: The Role Of Aceis In Cardiac Fibrosis In Rhdmentioning
confidence: 99%